Joint optimization method of failure probability and fiber-link load balancing in flexible bandwidth optical network - Bowen CHEN; Xiaodong FU; Yu LEI (Tongxin xuebao)
In order to gain insight into the relationship between the failure probability and the spectrum efficiency,both failure probability (FP) and load balancing (LB) were attempted to minimize in flexible bandwidth optical networks.An optimized FP-LB algorithm was developed to reduce failure probability and to improve the spectrum efficiency,and a traditional algorithm was further introduced for comparison in flexible bandwidth optical networks.Simulation results show that the optimized FP-LB algorithm reduces 69.8% blocking probability,45.3% spectrum occupancy rate,and 41.9% average failure probability compared to the traditional algorithm.Obviously,the optimized FP-LB algorithm achieves the joint optimization of both failure probability and load balancing.